Modelos de prácticas de física en el entorno natural para optimizar el aprendizaje de la energía potencial y cinética en los estudiantes del primer año de bachillerato del colegio particular para personas con escolaridad inconclusa Isidro Ayora Cueva de la ciudad de Loja, periodo 2014-2015 - Jaramillo Jaramillo, Juan Carlos (2015)
The theme of this research work is MODELS OF PRACTICE OF PHYSICS IN THE NATURAL ENVIRONMENT TO OPTIMIZE THE LEARNING OF THE POTENTIAL AND KINETIC ENERGY IN THE STUDENTS OF THE FIRTS YEAR OF HIGH SCHOOL OF THE PRIVATE SCHOOL FOR PEOPLE WITH UNFINISHED SCHOOLING ISIDRO AYORA CUEVA LOJA'S CITY, PERIOD 2014-2015. To perform this research work was raised as general purpose modeling practices of Physics in the natural environment to optimize the learning of the potential and kinetic energy in the students of the first year of high school of the Particular College for people with schooling unfinished Isidro Ayora Cueva Loja's city, period 2014-2015. For the development of the research it was done using the following methods: scientific method, inductive method, deductive method, method of analysis, synthesis and understanding, diagnosis method, modeling method, educational workshop method and the statistical method of measurement effectiveness. De the most outstanding results, determines there is presence of learning disabilities the most significant since the criteria of the teaching are: a receiver information rather than theoretical student that it evolves individually apart from communication with others, to learn socially, and that does not exercise their skills potential given the theorist nature of learning. Learning difficulties from the point of view of the student, expressed in resistance to work in cooperative teams, difficulties to make known its autonomous production and lack of arguments to analyze and discuss the practices of physics and research projects are also added. Based on the results we conclude that it is not giving due importance to learning through work strategies in cooperative groups, socialization of autonomous work of the student or laboratory practice activities. Situation that allows to recommend the use of alternative models of physical practices in the natural environment based on actual practices and cooperative work to optimize the learning potential and kinetic energy in students.